International symposium on peripheral nerve repair and regeneration and 2nd club Brunelli meeting - Turgut, Mehmet; Geuna, Stefano (Journal of Brachial Plexus and Peripheral Nerve Injury, 2010)
The International Symposium “Peripheral Nerve Repair and Regeneration and 2nd Club Brunelli Meeting” was held on December 4-5, 2009 in Turin, Italy (Organizers: Bruno Battiston, Stefano Geuna, Isabelle Perroteau, Pierluigi Tos). Interest in the study of peripheral nerve regeneration is very much alive because complete recovery of nerve function almost never occurs after nerve reconstruction and, often, the clinical outcome is rather poor. Therefore, there is a need for defining innovative strategies for improving the success of recovery after nerve lesion and repair and this meeting was intended to discuss, from a multidisciplinary point of view, some of today’s most important issues in this scientific field, arising from both basic and clinical neurosciences.